A Thermally Induced Perovskite Crystal Control Strategy for Efficient and Photostable Wide‐Bandgap Perovskite Solar Cells. Issue 6 (16th April 2020) - Kim, Geunjin; Moon, Chan Su; Yang, Tae-Youl; Kim, Young Yun; Chung, Jaehoon; Jung, Eui Hyuk; Shin, Tae Joo; Jeon, Nam Joong; Park, Helen Hejin; Seo, Jangwon
Abstract : Wide‐bandgap perovskite solar cells (WBG PSCs) have gained attention as promising tandem partners for silicon solar cells due to their complementary absorption, superb open‐circuit voltage, and an easy solution process. Recently, both their performance and stability have been improved by compositional engineering or defect passivation strategies, due to the modulation of perovskite crystal size and reduction of crystal defects. Herein, a report on the thermally induced phase control (TIPC) strategy is provided, which enables efficient and photostable WBG PSCs without compositional engineering by exploring a thermal annealing process window (100–175 °C and 3–60 min) of the WBG perovskite films. Within this window, a key annealing regime is found that produces preferred crystal orientations of lead iodide and the WBG perovskite, suppressing phase segregation and reducing charge recombination in the perovskites. The WBG PSCs (composition of FA0.75 MA0.15 Cs0.1 PbI2 Br and E g of 1.73 eV) optimized by TIPC exhibit an excellent power conversion efficiency (PCE) of 18.60% and improved operational stability, maintaining >90% of the maximum PCE (during maximum power point tracking) without encapsulation after 12 h of operation (air mass 1.5 global irradiation in ambient air conditions) or after 500 h of operation (white light‐emitting diode irradiation (100 mW cm −2 ) in N2 conditions). Abstract : By varying thermal annealing conditions, a thermally induced perovskite crystal control process of the wide‐bandgap perovskite films provides an opportunity to exploit both lead‐iodide passivation and perovskite orientation strategies with a fixed E g of 1.73 eV. Based on this concept, the device efficiency is improved from 15.76% to 18.60% and the operational photostability is also enhanced without any encapsulation in ambient conditions.